Radiomics Signatures Based on Computed Tomography for Noninvasive Prediction of CXCL10 Expression and Prognosis in Ovarian Cancer - Xiaohua Wang; Yuanyuan Xing; Xuan Zhou; Chunhui Wang; Shuyu Han; Sufen Zhao (Cancer Reports)
ABSTRACT Background Ovarian cancer (OC) is an aggressive gynecological tumor usually diagnosed with malignant ascites and even observed widespread metastasis or distant spread. Aims We aimed to develop and identify radiomics models according to computed tomography (CT) for preoperative prediction of CXCL10 expression and prognosis in patients with OC. Methods Genomic data with CT images and corresponding clinicopathological parameters were extracted from The Cancer Imaging Archive (TCIA) and The Cancer Genome Atlas (TCGA). To analyze the prognosis, we carried out the univariate Cox regression analysis (UCRA), multivariate Cox regression analysis (MCRA), and Kaplan–Meier (KM) analysis. For the data reduction, logistic regression, operator regression, least absolute shrinkage selection, radiomic feature construction, and feature selection were utilized. The predictive performance of the radiomic signatures was assessed using the analyses of the receiver operating characteristic (ROC) curve, decision curve (DCA), and precision‐recall (PR) curve. To evaluate the correlation between the radiomic score (Rad‐score) and CXCL10 expression, the Wilcoxon rank‐sum test was applied. Results Three radiomics models effectively predicted CXCL10 expression levels (AUC = 0.791, 0.748, and 0.718 for the set of training; AUC = 0.761, 0.746, and 0.701 for the set of validation). A higher Rad‐score significantly correlated with upregulated CXCL10 expression. Conclusion CXCL10 expression can be predicted noninvasively and preoperatively via radiomic signatures based on contrast‐enhanced CT images.